Role of DNA methylation in HPV associated lesions - Knebel Doeberitz, Magnus von; Prigge, Elena-Sophie (Papillomavirus Research, 2019)
Papillomavirus replication is tightly linked to squamous epithelial differentiation which in turn is governed to a large extent by epigenetic remodeling of genomes within the differentiating squamous epithelial cells. Over the past years it became evident that epigenetic and in particular differential methylation events substantially contribute to the regulation of the papillomavirus life cycle. Moreover, there is now good evidence that the initial trigger for HPV-mediated transformation of squamous epithelial cells is mediated by methylation of distinct CpG dinucleotides within E2-binding sites of the papillomavirus upstream regulatory region (URR). These findings have important implications for novel diagnostic markers but also for novel and indeed targeted therapy strategies for HPV linked neoplastic lesions.
Gesehen am 20.04.2020